2012
DOI: 10.4172/2155-9600.1000141
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Load and Keeping Quality of Kunu under Various Preservative Regimes

Abstract: Kunu beverage was prepared from two different cereals (Millet and Guinea corn), by standard native procedures the process of cleaning, steeping, wet milling; wet sieving, settling, decantation and slurry recovery were applied in its preparation. The following preservatives: lime, lemon, Phyllanthus, Sodium benzoate and a combination of 'Lime and Lemon' as mixed preservatives were added under cold and room temperatures and shelf-life monitoring was carried out. The sensory qualities (colour, taste, texture, fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…The mean scores of sensory evaluation, which revealed that the formulated malted/fermented and fortified foods were liked very much compared with the unmalted/unfermented foods which are moderately and slightly liked. The panelist observed that malted/fermented blend food were more acceptable in terms of taste (8.5), flavor (5.4), colour (6.5) and texture (6.5) as compared to malted/fermented food product as similar to the report of Fapounda and Adeware (2012) who revealed that the statistical analysis of the overall acceptability showed significant differences from 7.5 for malted/fermented product and 8.5 for malted/fermented blend product Green conidia present with lemon-shaped.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The mean scores of sensory evaluation, which revealed that the formulated malted/fermented and fortified foods were liked very much compared with the unmalted/unfermented foods which are moderately and slightly liked. The panelist observed that malted/fermented blend food were more acceptable in terms of taste (8.5), flavor (5.4), colour (6.5) and texture (6.5) as compared to malted/fermented food product as similar to the report of Fapounda and Adeware (2012) who revealed that the statistical analysis of the overall acceptability showed significant differences from 7.5 for malted/fermented product and 8.5 for malted/fermented blend product Green conidia present with lemon-shaped.…”
Section: Resultssupporting
confidence: 72%
“…The panelists were instructed to sip water before and after assessing each product. The judges recorded sensory characteristics of each sample using 9-point hedonic scale as described by Fapounda and Adeware (2012). Scoring with 9 being like extremely, 8 being like very much, 7 being like moderately, 6 being like slightly, 5 being neither like nor dislike, 4 being dislike slightly, 3 being dislike moderately, 2 being dislike very much and 1 being dislike extremely.…”
Section: Sensory Evaluation Of Fortified Malted-fermented and Unmaltementioning
confidence: 99%
“…On the other hand, juice samples treated with lime extracts was more effective on reduction of viable count of the yeast species than those treated with lemon extracts as seen from the results (Table 1). The result agreed with the report of Fapohunda et al [17] who recorded a decrease in microbial population (CFU/ml) of Kunu Zaki treated with lime and lemon juice in a quest to prolong its storage period.…”
Section: Plate 1a Schizosaccharomyces Japonicas On Sabouraud Dextrose Agarsupporting
confidence: 92%
“…15 Probiotic bacteria ease digestive distress, lower cholesterol level, slow down ageing process, boost energy and improve immunity. 11,15,16 In addition, lactic acid bacteria activate the synthesis and assimilation of vitamin C and minerals in the body. 11,16 Spices such as the ginger, clove and black pepper are used in the production of KZ in order to improve its taste, and ginger is widely used for culinary purposes in baked products.…”
Section: Production Of Kz From Millet Maize and Sorghummentioning
confidence: 99%
“…4,22,23 The sensory and keeping quality of KZ might improve by the addition of ginger solution concentrates in a certain proportion so that shelf life and storage optimization can be improved. 16…”
Section: Safety and Quality Issues Associated With Kzmentioning
confidence: 99%